Differential effects of psychological distress on mitigation and vaccination: A public health conundrum - Myerson, Joel; Strube, Michael J; Green, Leonard; Hale, Sandra; Bernstein, Bridget (Frontiers in Psychology, 2022)
CDC-recommended mitigation behaviors and vaccination status were assessed in an online sample (N=810; ages 18-80). Results were consistent with a differential distress hypothesis positing that whereas psychological distress, which is induced in part by social deprivation, interferes with mitigation behaviors involving social distancing, it motivates vaccination, in part because it, in turn, can increase social interaction. Age modulated these effects. Despite the greater risk of severe consequences, older adults not only showed less distress, but compared to younger participants with equivalent levels of distress, the older adults showed less effect of distress on both social distancing and vaccination status. Together these findings highlight a conundrum faced in public health messaging. Traditional ‘fear messages’ may be less effective for older adults, who are most in danger, whereas in younger adults, the distress induced by fear messages may motivate vaccination but diminish mitigation behaviors needed to prevent subsequent ‘breakthrough’ infections.